2017
DOI: 10.1039/c7ib00023e
|View full text |Cite
|
Sign up to set email alerts
|

Real-time quantification of endothelial response to shear stress and vascular modulators

Abstract: Quiescence is commonly used to describe the inactive state of endothelial cells (ECs) in monolayers that have reached homeostasis. Experimentally quiescence is usually described in terms of the relative change in cell activity (e.g. turnover, speed, etc.) in response to a perturbation (e.g. solute, shear stress, etc.). The objective of this study is to provide new insight into EC quiescence by quantitatively defining the morphology and activity of confluent cell monolayers in response to shear stress and vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 62 publications
(96 reference statements)
3
34
0
Order By: Relevance
“…To assess cell motility, we measured the average cell speed, the RMS displacement, and the directionality. The average cell speed, a measure of cell activity [ 11 , 26 , 33 ], was calculated by automated particle image velocimetry (PIV) analysis [ 19 ]. The average speed within the monolayers decreased from a maximum of approximately 0.2 µm min −1 during the 6-h conditioning period, to a steady state value of about 0.1 µm min −1 under static conditions and under 4 and 12 dyne cm −2 shear stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess cell motility, we measured the average cell speed, the RMS displacement, and the directionality. The average cell speed, a measure of cell activity [ 11 , 26 , 33 ], was calculated by automated particle image velocimetry (PIV) analysis [ 19 ]. The average speed within the monolayers decreased from a maximum of approximately 0.2 µm min −1 during the 6-h conditioning period, to a steady state value of about 0.1 µm min −1 under static conditions and under 4 and 12 dyne cm −2 shear stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the net rate of change in cell number (% h −1 ), the apoptosis rate was subtracted from the division rate. Identification of apoptosis and proliferation events from phase contrast movies allows quantitative analysis of the dynamic behavior of the monolayer as a function of time [ 33 , 34 ]. Furthermore, direct observation ensures that we include apoptosis events associated with cell loss and removal from the monolayer by shear flow, which may not be detected by labeling methods.…”
Section: Methodsmentioning
confidence: 99%
“…While these effects have been broadly documented across ECs of other organs, the response of BMECs to shear stress appears unique. While human umbilical vein endothelial cells (HUVECs) elongate in the direction of flow, BMECs instead remain rounded [ 41 , 42 ]. Other physical characteristics of capillaries, such as the degree of vessel curvature, have been shown to elicit elongation and alignment from HUVECs but not from immortalized BMECs, providing further evidence of their unique phenotype [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 DeStefano et al observed lower cell proliferation rates and higher apoptosis rates of EC at lower shear stress levels (4 dyn/cm 2 ) in comparison to higher WSS levels (16 dyn/cm 2 ). 49 Our results show cell proliferation between day 3 and day 21, where cell proliferation must overcome apoptosis or cell detachment because density is significantly higher on day 21 in comparison to days 3, 7, and 14.…”
Section: Discussionmentioning
confidence: 55%